2021
DOI: 10.3390/su13147831
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Life-Cycle Assessment and Life-Cycle Cost Analysis of a High-Rise Mass Timber Building: A Case Study in Pacific Northwestern United States

Abstract: Global construction industry has a huge influence on world primary energy consumption, spending, and greenhouse gas (GHGs) emissions. To better understand these factors for mass timber construction, this work quantified the life cycle environmental and economic performances of a high-rise mass timber building in U.S. Pacific Northwest region through the use of life-cycle assessment (LCA) and life-cycle cost analysis (LCCA). Using the TRACI impact category method, the cradle-to-grave LCA results showed better e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 35 publications
0
25
2
Order By: Relevance
“…The global building stock, which primarily uses concrete and steel, is projected to double over the next 40 years, with most of that growth expected to occur in the southern hemisphere. To reduce the impact of this building expansion, MT buildings may offer a potentially appealing alternative to concrete and steel [11,[21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global building stock, which primarily uses concrete and steel, is projected to double over the next 40 years, with most of that growth expected to occur in the southern hemisphere. To reduce the impact of this building expansion, MT buildings may offer a potentially appealing alternative to concrete and steel [11,[21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-building LCA (WBLCA) studies have quantified and compared the environmental impact of MT buildings with that of traditional concrete and steel structures [11][12][13]21,22,[25][26][27][28]. In one case study of midrise buildings [11], total carbon emissions for a five-story MT building were dominated by the manufacturing stage (77%), while the construction stage represented only 3% of the total carbon emissions.…”
Section: Introductionmentioning
confidence: 99%
“…This study and related findings serve as a precedent for our research in the U.S. The study by Liang et al [17] even considered four scenarios of CLT transportation from abroad (Austria, Canada) and from local origin (northwest region of the U.S.) to the site. The results show a dramatic variation ranging between 3.4 to In the existing literature, however, there is data on domestic transportation of other materials, but the environmental impacts resulting from the CLT import are not very well comprehended.…”
Section: Introductionmentioning
confidence: 94%
“…This study and related findings serve as a precedent for our research in the U.S. The study by Liang et al [17] even considered four scenarios of CLT transportation from abroad (Austria, Canada) and from local origin (northwest region of the U.S.) to the site. The results show a dramatic variation ranging between 3.4 to 47 kg CO 2 -eq per m 2 mass timber floor area, which calls for more studies to confirm or dispute these outcomes.…”
Section: Introductionmentioning
confidence: 94%
“…The results highlighted that the refurbishment of existing buildings had the lowest environmental impact on all impact categories, and the difference in environmental impacts between new building types was generally small, while the CLT and wood-frame buildings still had the best environmental performance. Liang et al [ 75 ] examined a high-rise mass-timber building in the Pacific Northwest using LCA and life-cycle cost analysis approaches to assess the life-cycle environmental and economic performances and compared these results to for a concrete building of the same design. Cradle-to-grave (modules A–C) LCA results, which have been in operation for over 60 years, showed that the mass-timber building outperformed the concrete building in terms of global warming (1.6% lower) and other environmental impacts.…”
Section: Introductionmentioning
confidence: 99%